Islamic Republic of Mauritania : 2009 Article IV Consultation and Request for a Three-Year Arrangement Under the Extended Credit Facility; Staff Report; Public Information Notice and Press Release on the Executive Board Discussion; and Statement by the Executive Director for the Islamic Republic of Mauritania. (IMF Staff Country Reports; Country Report ;, 2010)
This Article IV Consultation reports that the economic growth of Mauritania is robust, which reflected prudent economic management, sustained donor support, and the beginning of oil production. Executive Directors observed that the return of constitutional order to Mauritania has established a basis for the resumption of the reform agenda and of financial support from the international community. They commended the authorities' commitment to protect poverty-related spending. They also highlighted the need to expand and strengthen safety nets and social protection.